Determination of risk factors affecting mortality in patients with - Barut, B; Akbulut, S; Kutluturk, K; Koc, C; Ozgor, D; Aydin, C; Selimoglu, A; Yilmaz, S (2019)
Gastrointestinal perforation (GIP) is one of the most serious complications occurring after liver transplantation (LT), especially in pediatric patients. This study aimed to determine the risk factors affecting mortality in pediatric patients with GIP after LT. GIP developed in 37 (10%) of 370 pediatric patients who underwent LT at our institute. Patients were divided into two groups: alive (n = 22) or dead (n = 15), and both groups were compared in terms of demographic and clinical parameters using univariate analysis. There was no statistically significant difference between groups in either demographic or clinical parameters, except for perforation site (P = 0.001) and median follow-up (P = 0.001). Stomas arose in 17 (45.9%) patients: 76% of patients with stomas and 45% of those without survived (P = 0.052). Kaplan-Meier analysis indicated that patients with stomas had a significantly higher overall survival (P = 0.029) and that patients with duodenal and colonic perforation had a significantly lower overall survival. Multivariate analysis showed that re-perforation was an independent risk factor for mortality (P = 0.035; OR: 17.674; 95% CI for OR: 1.233-253.32). Although there are many options for management of GIP, including primary repair, resection plus anastomosis, and resection plus end or loop ostomy, gastrointestinal diversion is still the best option. C1 [Barut, Bora; Akbulut, Sami; Kutluturk, Koray; Koc, Cemalettin; Ozgor, Dincer; Aydin, Cemalettin; Yilmaz, Sezai] Inonu Univ, Fac Med, Liver Transplant Inst, Malatya, Turkey. [Selimoglu, Ayse] Inonu Univ, Fac Med, Dept Pediat Gastroenterol, Malatya, Turkey.